From Esthetic Medicine to Optimizing Reconstructive Outcome: A Feasibility Trial on Secondary Refinement of Fasciocutaneous Anterolateral Thigh Flaps with Cryolipolysis - Nagel, Sarah S.; Rauh, Annika; Siegwart, Laura C.; Hundeshagen, Gabriel; Kotsougiani-Fischer, Dimitra; Kuepper, Simon; Kneser, Ulrich; Hirche, Christoph (Journal of Reconstructive Microsurgery, 2022)
Background Free adipocutaneous anterolateral thigh (ALT) flaps have evolved as workhorse flaps to reconstruct complex, multicompound defects. While coverage is safely achieved, flaps may remain bulky. As a standard of care, flaps are refined with liposuction, partial excision, or combination of both. Cryolipolysis is widely used for fat reduction in esthetic medicine. This pilot comparative study analyses whether cryolipolysis may serve as a safe alternative method to effectively reduce volume in fasciocutaneous flaps. Moreover, patients' satisfaction with the procedure is evaluated.Methods In this single-center, retrospective, interventional comparative cohort study, 10 patients with free subfascial ALT flaps for distal extremity reconstruction underwent cryolipolysis (60 minutes, −9°C). Circumference of the extremities and subcutaneous fat thickness were determined before (T1) and 12 weeks (T2) after cryolipolysis. Patient satisfaction was evaluated with a questionnaire of Likert's scale questions. Duration of hospital stay, intervention time, costs, and possible complications were analyzed and compared with surgical flap contouring (n = 12).Results All patients undergoing cryolipolysis were male, with a median age of 52 years without arterial disease-like state or deep vein thrombosis (DVT). At T2, a significant reduction of circumference of 1.8 ± 0.9 cm (p < 0.001) and subcutaneous fat layer of 7.7 ± 3.0 mm (p < 0.0001) was recorded. Overall, 90% of the patients were satisfied with the result. Cryolipolysis was well tolerated. One patient developed a second-degree frostbite which healed without further intervention. Cryolipolysis proofed to be as safe as surgical flap contouring. Hospital stay was significantly shorter (p < 0.01) and personal resources were spared when flap contouring was performed with cryolipolysis.Conclusion This is a novel application of evolving body-contouring cryolipolysis from esthetic medicine into optimizing outcomes in reconstructive surgery. Cryolipolysis has been shown to be relatively safe and effective to reduce ALT's volume with high patients' satisfaction. This successful pilot study encourages further investigation with a prospective randomized control trial.
Keywords: cryolipolysis; secondary refinement; ALT; bulky free flap; subfascial